Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 12 - Section 12.6 - Integrated Review - Functions and Properties of Logarithms - Page 883: 2



Work Step by Step

f(x)=x-6 and g(x)=$x^{2}$+1 (f-g)(x)=(x-6)-($x^{2}$+1)=x-6-$x^{2}$-1= -$x^{2}$+x-7
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.